2020
DOI: 10.21203/rs.2.19600/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Determinants of Malaria Infection Among Children of local farmers in Central Malawi

Abstract: Background: Malaria is a leading cause of morbidity and mortality among children under five in Malawi. Children from rural areas of central Malawi have a high burden of malaria morbidity compared to other regions. The goal of this study was to examine the prevalence and determinants of malaria infection among children in rural areas of the Dowa district in central Malawi.Methods: A multistage cross-sectional study design was used to systematically sample 523 child‑mother dyads from postnatal clinics. A survey … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
8
3
2
Order By: Relevance
“…This finding is consistent with the literature in SSA that found that marital infidelity by men was a significant trigger of IPV against women [1,49]. Studies have shown that when women confront their partners after discovering their infidelity, some partners respond aggressively, which can escalate into emotional or physical violence [50].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with the literature in SSA that found that marital infidelity by men was a significant trigger of IPV against women [1,49]. Studies have shown that when women confront their partners after discovering their infidelity, some partners respond aggressively, which can escalate into emotional or physical violence [50].…”
Section: Discussionsupporting
confidence: 91%
“…No difference was found between sex in this study. Similar results were reported in Chimoio, Mozambique in 2018 17 , in Malawi in 2020 21 and in Zimbabwe 22 in 2021.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, women with partners who had extra marital sexual affairs were at greater risk for experiencing controlling, psychological, and physical violence than women who reported that their partners did not had extra marital affairs. This nding is consistent with the literature in SSA that found that marital in delity by men was a signi cant trigger of IPV against women [54,55]. Studies have shown that when women confront their partners after discovering their in delity, some partners respond aggressively, which can escalate into emotional or physical violence [56].…”
Section: Discussionsupporting
confidence: 91%